The Significance of Social Entrepreneurship in Generating Solutions to Social and Economic Challenges - Rhena J; Hayadin, Muh Ridwan; Amory, Jeffriansyah Dwi Sahputra (PT. LITERASI SAINS NUSANTARA, 2023)
In a global context, we face various complex social and economic challenges such as poverty, income inequality, unemployment, limited access to education and healthcare services, as well as environmental issues like environmental degradation and climate change. This research aims to identify the significance of social entrepreneurship in generating solutions to social and economic challenges. The method used in this research is a qualitative literature review drawing data from Google Scholar for the period 2004-2023. This study will conduct an in-depth analysis of various relevant articles, papers, and scientific publications found through the Google Scholar platform. The results of the study indicate that social entrepreneurship holds significant importance in addressing complex social and economic challenges worldwide. Through innovative, socially and environmentally oriented approaches, social entrepreneurship has proven itself as a force capable of bringing about significant positive impacts. From alleviating poverty to promoting environmental sustainability, the social entrepreneurship movement has inspired meaningful changes in how we think about business and development.